The adoption problem is a matter of fit: tracing the travel of pruning practices from research to farm in Ghana’s cocoa sector - Adomaa, Faustina Obeng; Vellema, Sietze R.; Slingerland, M.; Asare, R. (Springer, 2022)
Good Agricultural Practices (GAPs) are central to sustainability standards and certification programmes in the global cocoa chain. Pruning is one of the practices promoted in extension services associated with these sustainability efforts. Yet concerns exist about the low adoption rate of these GAPs by smallholder cocoa farmers in Ghana. A common approach to addressing this challenge is based on creating enabling conditions and offering appropriate incentives. We use the concepts of inscription and affordance to trace the vertically coordinated travel of recommended pruning from research to extension and farming sites, and to describe how pruning is carried out differently at each site. Our analysis suggests that enactments of pruning at the extension site reduce the number of options and space for interactions and this constrains making the practice meaningful to farmers’ repertoires. The conventions guiding and legitimizing actions at this site, reinforced by sustainability standards, certification schemes and associated inspections and audits, favour standardized recommendations and consequently narrow room for context-specific diagnostics and adaptions. Therefore, we reframe the adoption problem as a matter of fit between different sites in the ‘agricultural research value chain’ embedded in the operational cocoa chain. Our contribution problematizes the dominant framing of low adoption and highlights that the movement of pruning and the sequential enactment at different sites constrain the affordances available for rendering the practice meaningful to farmers’ repertoires. Consequently, addressing the low uptake of GAPs requires institutional work towards conventions that can construct a fit between sites along the agricultural research value chain.